Teacher agency in the dynamics of educational practices: a theory synthesis - Emans, Anita; Oolbekkink-Marchand, Helma; Bakker, Cok; De Bruijn, Elly (Frontiers in Education, 2025)
In this study, a theory synthesis was conducted from a sociocultural perspective to specify the situated processes involved in teacher agency development in the dynamics of educational practices. Agency is closely related to teacher wellbeing and important for teachers to create situations that enable them to act in line with their understanding of what is valuable and feasible. Both the policy landscape and the nature of educational processes, with their emphasis on routines and immediate actions, have had a constraining impact on teacher agency. We specified agency as a situated act that is intertwined with the sociocultural rooted structures and contexts that give rise to it, and in which it is enacted. We unpacked it as a mediating tool through which teachers, both individually and jointly, steer work processes. We brought together valuable insights from previous studies on processes that unfold in educational practices and that are involved in shaping teacher agency. To determine our focus, we conducted interviews with experts in the field of teacher agency research resulting in the study of four research domains. They include sensemaking processes, teacher collaboration processes, professional identity processes and organizational work processes. Based on our analysis, we identified twelve “agentic qualities”. These qualities enable recognizing expressions of agency within these processes. We consider studying the emergence and development of these “agentic qualities” in their interconnectedness as important for understanding the development of teacher agency. Suggestions for future research include empirically studying how these interconnected sociocultural processes are shaped in practice.